6,6-Diaryl Fulvenes. Reduction to Benzhydryl Cyclopentadiene by Amide Bases - Lorenz, Helmuth Heinrich (My University, 1969)
This work was started to investigate new methods of synthesizing certain fulvenes. It was hoped that nucleophilic aromatic substitution of chlorine on 6,6-bis-(p-chlorophenyl) fulvene would provide an alternate route for the preparation of para-substituted 6,6-diphenyl fulvenes which had previously been prepared through the appropriately para-substituted benzophenone and cyclo-pentadienide (1,2). Attempts to prepare these substituted 6,6-diphenylfulvenes were unsuccessful.
Secondly, a method of alkylating certain fulvenes in the cyclopentadiene ring was studied. With this in mind, 6,6-diphenylfulvene was treated with various nucleophiles which should give the relatively stable cyclopentadienide intermediate if the base adds to the exocyclic carbon atom. Alkylation of this anion, followed by expulsion of the nucleophilic group and a proton should then generate a new fulvene alkylated in the cyclopentadiene ring. In no case was any alkylated fulvene isolated. The major reaction products were two isomers of benzhydryl cyclopentadiene, rather than the expected alkylated fulvenes. The benzhydryl cyclopentadiene (mixture of two isomers) appears to have resulted from a reduction reaction.
Since fulvenes of the type under study are generally unstable, an attempt was made to trap these alkylated fulvenes, if these were present, as their Diels-Alder adducts with tetracyanoethylene (TCNE). This attempt gave the adduct from one of the isomers of benzhydryl cyclopentadiene. The adducts from the other two possible isomers of benzhydryl cyclopentadiene were not detected. This result is an indication of the different reactivities of these isomers to TCNE.
From the absence of TCNE adducts of the expected alkylated fulvenes, it was concluded that these fulvenes had not materialized in the attempted alkylation.
Keywords: diaryl fulvenes, amide bases, synthesizing, alkylated